(3eYLe GdSHcis - (3eMeO Hf jMji Hf eMeO Hf SYO GdebOSj,J (B759 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeg GdJi WGH MOjKgG s
(3GdfSNI ddYdGeI GdeMOK TgGH GdOjf GdMSGfi abQCgG Ydi GdeNQL dg JGL GdOjf GdSHci ceG jSJaGO HGdMhGTi GdeHfjI ehGVjYgG HChd GdLRA GdChds
(3YdjgG NW GdYdGeI GdSNGhis
(3LeYg di JGL GdOjf YHO GdhgGH Ydi GdSHci GdeJhai SfI (B771 (3g`s
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs